Perbaikan Bacaan Alquran melalui Kegiatan Tahsin al-Qiraah: Participatory Action Research di Aceh Tamiang - Zulham Zulham Khoir; Tiy Kusmarrabbi Karo; Slamet Riyadi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
Aceh Tamiang is an area with a majority Muslim population, not even one in Adil Makmur Village, Tenggulun, which is the location for this activity to find other places of worship besides mosques and prayer rooms. However, there is a decline in the quality of reading and writing the Koran in today's young generation compared to previous generations. This is due to the lack of parental attention to the quality of children's reading of the Koran, because they have fully surrendered this role to existing Koranic educational institutions. While in the previous generation, most parents were very disciplined for matters related to religious knowledge, especially reading and writing the Koran. The implementation of this Action Research aims to improve the literacy and writing skills of the young generation of the Koran in Adil Makmur Village, Tenggulun, Aceh Tamiang by empowering STAI As-sunnah students for Tahsin al-Qiraah activities. The method used is Participatory Action Research. By doing 3 stages: Planning-Action-Evaluation. The result of this activity: increased public enthusiasm for the importance of the younger generation having the ability to read and write the Koran in Adil Makmur Village, Tenggulun, Aceh Tamiang. In addition, this activity has also succeeded in making the role of parents as the main guides for children re-enforced